Research on casing damage risk early warning technology based on MIT-MTT logging and 16S rRNA gene analysis - Wang, Shuoliang; Wang, Shiqi; Li, Congcong; Zhou, Changhao; Jiang, Liangliang (Frontiers in Microbiology, 2025)
With the continuous advancement of oilfield development, the number of oil–water wells experiencing casing damage due to corrosion has increased annually, which has seriously affected the injection-production balance and significantly reduced the potential for recovering residual oil. Because the water cut trends in casing-damaged wells are similar to those in water breakthrough injection wells, identifying wells with casing damage has been challenging. This study is the first to combine the Multi-Finger Imaging Tool (MIT)-Magnetic Thickness Tool (MTT) integrated logging technology with 16S rRNA gene analysis to systematically analyze the relationship between casing damage and the composition of microbial communities. The results indicated that there were significant differences in the high-corrosion zones at various depths, and the structure of the sulfate-reducing bacterial community in the produced fluids also varied. In particular, in deeper zones, the relative abundance of thermophilic bacteria, represented by Thermotogata, increased significantly. Moreover, the more severe the casing damage, the more dominant the sulfate-reducing bacteria became in the microbial community of the produced fluids. After secondary sealing treatment, the proportion of sulfate-reducing bacteria was significantly reduced. The study further found that sulfate-reducing bacteria primarily belonged to the phyla Proteobacteria, Bacillota, Thermotogata, and Thermodesulfobacteriota, while significant populations of iron-reducing bacteria were not detected in the produced fluids. This finding suggests that sulfate-reducing bacteria are the main microbial factor causing metal corrosion of the casings. Innovatively, this study proposes a biometal corrosion monitoring method for production wells based on microbial community structure, thereby providing a novel technical approach to preventing oil well corrosion.